MODERN LABORATORY APPROACHES IN THE DIAGNOSIS OF CMV INFECTION IN IMMUNOCOMPROMISED PATIENTS - E. Iu. Padalko (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. High susceptibility of immunocomromised human to infection (especially transplant recipients) is influenced by poor ability to combat it due to impaired cellmediated immunity plus high vulnerability to perturbations in the environment. Special considerations regarding infection in transplant recipients and particular approaches in laboratory diagnostics are based on profound analysis of the nature of viral infection in this population. In this article the modern knowledge about viral infections and laboratory diagnostic methods, particularly regarding CMV infection, in immunocompromised patients are discussed.